Perovskite-porous carrier composite material and preparation method and application thereof

Through the synergistic effect of perovskite-porous carrier composites, the problems of low efficiency and short durability of existing disinfection methods are solved, and high-efficiency, long-term, safe and broad-spectrum antibacterial and antiviral effects are achieved.

CN119679940APending Publication Date: 2025-03-25JILIN UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411861594.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing disinfection methods have problems such as low efficiency, short duration and harmful to the human body and the environment in terms of disinfecting bacteria and viruses, and lack an efficient, long-term, safe and broad-spectrum disinfection material.

Method used

Perovskite-porous carrier composite material is used to achieve efficient and long-term antibacterial and antiviral effects through the photoresponsiveness of the perovskite material and the adsorption and protection of the porous carrier.

Benefits of technology

This composite material has good stability and broad spectrum, can effectively kill a variety of bacteria and viruses in a short period of time, and is less harmful to the human body and the environment and has strong durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119679940A_ABST
    Figure CN119679940A_ABST
Patent Text Reader

Abstract

The invention provides a perovskite-porous carrier composite material as well as a preparation method and application thereof, and belongs to the technical field of environmental medical health materials. The composite material comprises a porous carrier and a perovskite material loaded in the porous carrier. The photoresponsive antibacterial and antiviral performance of the perovskite material and the adsorption and protection effects of the porous carrier are utilized, and the host-guest synergistic effect of the perovskite material and the porous carrier is utilized, so that the perovskite-porous carrier composite material obtains good stability, and efficient, long-acting, safe and broad-spectrum antibacterial and antiviral effects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of environmental medical health materials, and specifically relates to a perovskite-porous carrier composite material and a preparation method and application thereof. Background Art

[0003] In order to better treat infections caused by drug-resistant bacteria, various antimicrobial drugs (e.g., antimicrobial peptides and amphiphiles) and antimicrobial materials (e.g., nanoparticles, hydrogels, engineered surfaces, and surface coatings) have been developed and applied. However, the situation of bacterial resistance has not been effectively alleviated. How to effectively kill bacteria without causing bacterial resistance has become an important research topic today. Bacteria can be adsorbed on the surface of materials under the action of Coulomb force, van der Waals force, or hydrogen bonding. Then the bacteria aggregate, the flagella degenerate, and begin to secrete the extracellular matrix (ECM) to achieve irreversible adhesion to the surface. Therefore, it is reasonable to develop effective strategies to interfere with the interaction between bacteria and material surfaces, which can be achieved by changing the morphology, hardness, roughness, and chemical composition, thereby hindering the communication between bacteria and ultimately delaying the formation of biofilms.

[0004] The rational use of disinfectants to clean the air, surfaces of public facilities and water sources in the environment can effectively reduce the infection of bacteria and viruses through aerosol transmission, contact transmission, sewage and drinking water transmission. Especially in crowded and closed public places such as hospitals and airports, regular use of disinfectants to thoroughly clean the environment is crucial to epidemic prevention and control. 75% ethanol and 0.1% sodium hypochlorite disinfectants can greatly reduce the number of bacteria and viruses in the air and on the surface of objects within 1 minute, and have become the main means of disinfection. In addition, in some specific places and environments, iodine tincture, ozone, hydrogen peroxide, ultraviolet rays, etc. also show good virus disinfection effects. However, the disinfection effect of these methods lasts for a short time, and the disinfection activity cannot be maintained for a long time. Long-term use is neither economical nor environmentally friendly; in addition, disinfectants are mostly highly oxidizing, which has great harm and corrosive effects on the human body and public facilities. So far, there is still a lack of an effective disinfection material that can simultaneously achieve high efficiency, long-term effectiveness, safety and broad spectrum of bacterial and viral disinfection. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a perovskite-porous carrier composite material and its preparation method and application. The present invention utilizes the synergistic effect of perovskite and porous carrier to make the composite material have good stability and high efficiency, long-term, safe and broad-spectrum antibacterial and antiviral effects.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a perovskite-porous carrier composite material, the composite material comprising: a porous carrier, and a perovskite material loaded in the porous carrier.

[0008] In the present invention, the perovskite material is a photoresponsive material, which has the advantages of low production cost and simple production process while having good semiconductor properties. Perovskite materials can produce active oxygen species (such as ozone free radicals, hydroxyl free radicals, etc.) under light, destroying the structure of microbial pathogens, thereby killing bacteria and viruses. The characteristics of perovskite materials with excellent weak light performance and adjustable photoelectric properties are not possessed by other traditional antibacterial and antiviral materials. However, since perovskite materials are ionic crystals with poor crystal stability, their structure is relatively fragile, and there are problems such as high temperature resistance, light resistance, easy hydrolysis, and easy oxidation, which limits their application in antibacterial and antiviral applications.

[0009] Porous carriers have rich pore structures that can provide space for the loading of perovskite materials. Taking molecular sieves as an example, they are a type of aluminosilicate crystals with regular pore structures, composed of [SiO4] and [AlO4] tetrahedrons through shared vertex oxygen atoms; the anionic framework structure formed needs to be balanced by additional cations, and its chemical formula can be expressed as M n / m (SiO2)(AlO2) n ·xH2O (M is a cation, and the valence state is m). Molecular sieves can non-specifically adsorb viruses through electrostatic effects, thereby inhibiting the adsorption of viruses to host cells. In addition, perovskite materials are more stable in the pores of porous carriers and can maintain antimicrobial pathogen activity for a longer period of time. The porous carrier has a slow-release protective effect on the disinfection active center, which can ensure lower human toxicity and environmental hazards.

[0010] The present invention utilizes the light-responsive antibacterial and antiviral properties of the perovskite material and the adsorption and protection effects of the porous carrier (host-guest synergistic effect), so that the perovskite-porous carrier composite material has good stability and achieves efficient, long-lasting, safe and broad-spectrum antibacterial and antiviral effects.

[0011] In some embodiments of the present invention, in the composite material, the mass content of the perovskite material is 0.1-2%, for example, 0.1%, 0.2%, 0.3%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.3%, 1.5%, 1.6%, 1.8% or 2%, etc. However, the present invention is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0012] In the present invention, if the content of the perovskite material in the composite material is too little, the antibacterial and antiviral effect of the composite material is poor, or even has no effect; if the content of the perovskite material in the composite material is too much, the human toxicity and environmental hazards of the composite material may increase, causing certain biological toxicity and resulting in a decrease in safety.

[0013] In some embodiments of the present invention, the particle size of the composite material is 100-500 nm.

[0014] In the present invention, if the particle size of the composite material is too small, the stability of the material may be reduced; if the particle size of the composite material is too large, the material may aggregate and settle, which is not conducive to application.

[0015] In some embodiments of the present invention, the perovskite material includes one or more of an oxide perovskite material, a halide perovskite material, a double perovskite material and an antiperovskite material.

[0016] In some embodiments of the present invention, the perovskite material is selected from one or more of ABX3, A2BX6, A3B2X5 and A2BX4, wherein A is selected from one or more of La, Ce, Cs, FA (formamidinium cation) and MA (methylamine cation), B is selected from one or more of Fe, Mn, Bi, Ag, In and Ti, and X is selected from one or more of O, Br, Cl and I.

[0017] In some embodiments of the present invention, the perovskite material is selected from one or more of LaFeO3, Cs2AgInCl6, Cs2AgBiBr6, MA2AgSbI6, Cs3Cu2I5 and CeMnO3.

[0018] In some embodiments of the present invention, the porous carrier includes one or more of a molecular sieve, an inorganic mesoporous material and an inorganic macroporous material.

[0019] In some embodiments of the present invention, the porous carrier is selected from one or more of a molecular sieve and a metal organic framework.

[0020] In the present invention, different carriers can be selected according to different practical application requirements.

[0021] In some embodiments of the present invention, the pore size of the molecular sieve is less than 2 nm, and the molecular sieve includes one or more of X,Y type molecular sieve, A type molecular sieve, silicate-1 molecular sieve, ZSM-5 molecular sieve and beta molecular sieve.

[0022] In some embodiments of the present invention, the pore size of the inorganic mesoporous material is 2-50 nm, and the inorganic mesoporous material includes one or more of mesoporous silicon, mesoporous metal organic frameworks (MOFs), mesoporous covalent organic frameworks (COFs) and mesoporous metal oxides.

[0023] In some embodiments of the present invention, the pore size of the inorganic macroporous material is greater than 50 nm, and the inorganic macroporous material includes one or more of a macroporous metal organic framework, a macroporous ceramic, and a macroporous oxide.

[0024] In some embodiments of the present invention, the metal organic framework includes one or more of isoreticular MOFs (IRMOFs), zeolite-imidazolate frameworks (ZIFs), materials of Institute Lavoisier (MILs) and pocket-channel frameworks (PCNs).

[0025] In a second aspect, the present invention provides a method for preparing the perovskite-porous carrier composite material as described in the first aspect, wherein the preparation method is a solution method or a solid phase calcination method;

[0026] The solution method comprises: dissolving a precursor of a perovskite material in an organic solvent, mixing the mixture with a porous carrier, performing a first heat treatment to allow the precursor to enter the pores of the porous carrier, separating a solid product, and performing a second heat treatment to convert the precursor into a perovskite material to obtain the perovskite-molecular sieve composite material;

[0027] The solid phase calcination method comprises: mixing a precursor of a perovskite material with a porous carrier, and calcining the mixture to obtain the perovskite-porous carrier composite material.

[0028] In the present invention, the type of the precursor can be conventionally selected according to the type of perovskite material. For example, for oxide perovskite materials, the precursor can be chlorides, acetates, nitrates, etc. of various non-oxygen elements in oxide perovskite materials; for halide perovskite materials, the precursor can be halides of various non-halogen elements in halide perovskite materials.

[0029] In some embodiments of the present invention, the organic solvent includes N,N-dimethylformamide (DMF) and / or dimethyl sulfoxide (DMSO).

[0030] In some embodiments of the present invention, the temperature of the first heat treatment is 30-200°C, for example, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, etc. However, the present invention is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0031] In some embodiments of the present invention, the first heat treatment time is 2-4 hours, for example, 2 hours, 2.2 hours, 2.5 hours, 2.8 hours, 3 hours, 3.2 hours, 3.5 hours, 3.8 hours or 4 hours, etc. However, the present invention is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0032] In some embodiments of the present invention, the temperature of the second heat treatment is 200-500°C, for example, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 320°C, 330°C, 350°C, 360°C, 380°C, 400°C, 420°C, 430°C, 450°C, 460°C, 480°C or 500°C, etc. However, the present invention is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0033] In some embodiments of the present invention, the second heat treatment time is 1-4 hours, for example, 1 hour, 1.2 hours, 1.5 hours, 1.8 hours, 2 hours, 2.2 hours, 2.5 hours, 2.8 hours, 3 hours, 3.2 hours, 3.5 hours, 3.8 hours or 4 hours, etc. However, the present invention is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0034] It should be noted that, in the present invention, the conditions of the first heat treatment and the second heat treatment are different according to the type of perovskite material. Those skilled in the art can make a selection according to the properties of the precursor and the perovskite material to ensure that the precursor is fully loaded into the porous carrier and fully converted into the perovskite material. As a non-limiting example, when the perovskite material is an oxide perovskite material, the temperature of the first heat treatment can be 100-200°C, and the temperature of the second heat treatment can be 300-500°C; when the perovskite material is a halide perovskite material, the temperature of the first heat treatment can be 30-100°C, and the temperature of the second heat treatment can be 200-300°C.

[0035] In some embodiments of the present invention, the solution method further comprises: washing the solid product before performing the second heat treatment.

[0036] In some embodiments of the present invention, the solvent used for washing includes water and / or ethanol.

[0037] In some embodiments of the present invention, the calcination temperature is 500-800° C., for example, 500° C., 520° C., 550° C., 580° C., 600° C., 620° C., 650° C., 680° C., 700° C., 720° C., 750° C., 780° C. or 800° C. However, the present invention is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0038] In some embodiments of the present invention, the calcination time is 4-8 hours, for example, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours, etc. However, the present invention is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0039] In a third aspect, the present invention provides a perovskite-porous carrier composite material as described in the first aspect, or a perovskite-porous carrier composite material prepared by the preparation method described in the second aspect, and its use in the preparation of antibacterial and antiviral products, anti-tumor drugs, bioimaging agents or thermal diagnosis and treatment photothermal agents.

[0040] In some embodiments of the present invention, the antibacterial and antiviral products include disinfectants and wound dressings.

[0041] The perovskite-porous carrier composite material provided by the present invention has high efficiency, long-acting, safe and broad-spectrum antibacterial and antiviral effects. For the application of antibacterial and antiviral aspects, the composite material has a variety of application forms. For example, the composite material can be used alone or mixed with a solvent as a disinfectant, sprayed in the environment, to achieve environmental disinfection, and to curb the spread of emerging sudden virulent pathogens including monkeypox virus in the natural environment. It can also be dispersed in existing dressings (such as medical nonwovens, gels, fibers, bandages, etc.), as wound dressings, to promote the healing of bacterial and viral infection wounds.

[0042] In the present invention, the types of bacteria and viruses targeted by the antibacterial and antiviral products include but are not limited to: Staphylococcus aureus, Helicobacter pylori, Escherichia coli, Bacillus anthracis, Brucella, Clostridium tetani, Treponema pallidum, herpes virus, hepatitis B virus, HIV, hemorrhagic fever virus, influenza virus, new coronavirus, and monkeypox virus.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] The perovskite-porous carrier composite material provided by the present invention has good stability, and high efficiency, long-term, safe and broad-spectrum antibacterial and antiviral effects. The composite material is non-irritating, has no toxic effects on the human body, and has good biocompatibility; the disinfecting efficiency of monkeypox virus within 5 minutes is ≥99.99%; it can be stably stored in different solvent systems (such as water, ethyl acetate, acetonitrile, ethanol, methanol, etc.) or in the air for more than 12 months, and the structure and performance remain stable.

[0045] The preparation method of the perovskite-porous carrier composite material provided by the present invention is simple and easy to realize industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is a data graph showing the in vitro anti-monkeypox virus performance of the perovskite-molecular sieve composite material provided in Examples 1-3 of the present invention.

[0047] Figure 2 TEM images of monkeypox virus particles before and after treatment with the perovskite-molecular sieve composite material provided in Example 1.

[0048] Figure 3 This is a graph showing the weight changes of mice injected with the solution of the perovskite-molecular sieve composite material provided in Example 1 through the tail vein and mice in the control group.

[0049] Figure 4 These are staining images of heart, liver, spleen, lung, and kidney tissue sections of mice injected with the solution of the perovskite-molecular sieve composite material provided in Example 1 through the tail vein and mice injected with PBS through the tail vein.

[0050] Figure 5 Pathological section staining images of the tail lesion area of ​​the monkeypox virus infected mouse tail scratch model treated with and without external application of the perovskite-molecular sieve composite material provided in Example 1.

[0051] Figure 6 Graph showing the healing effects of the skin area of ​​New Zealand rabbits infected with monkeypox virus with and without application of the perovskite-molecular sieve composite material provided in Example 1.

[0052] Figure 7 The fluorescence rate data graph is a graph of A549 cells infected with VSV-GFP virus at different times after being treated with the perovskite-MOFs composite material provided in Examples 4-6.

[0053] Figure 8 The data graph is a viral titer data of the nasal concha, trachea and lung tissue homogenates of golden hamsters infected with SARS-CoV-2 virus after being treated with the perovskite-MOFs composite materials provided in Examples 4-6. DETAILED DESCRIPTION

[0054] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementations. It should be understood by those skilled in the art that the specific implementations are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0055] Example 1

[0056] This embodiment provides a perovskite-molecular sieve composite material, including a molecular sieve and a perovskite material loaded in the molecular sieve, and the preparation method thereof is as follows:

[0057] 0.6 mol CsI and 0.4 mol CuI were dissolved in 12 mL organic solvent N,N-dimethylformamide (DMF), and 1.2 g ZSM-5 molecular sieve (purchased from Luoyang Jianlong Micro-Nano New Materials Co., Ltd.) was added. The mixture was heat treated at 80 °C for 3 h under stirring. The solid product was separated by centrifugation, washed with water and ethanol for 5 times, and then heat treated at 260 °C for 3 h to obtain a perovskite-molecular sieve composite material. 50 The particle size is 300nm and the content of perovskite material (Cs3Cu2I5) is 1.7wt%.

[0058] Example 2

[0059] This embodiment provides a perovskite-molecular sieve composite material, which is different from Example 1 only in that the raw material dosage is CsI0.25mol, CuI0.16mol, and ZSM-5 molecular sieve 1.2g, and the content of perovskite material (Cs3Cu2I5) in the composite material is 0.7wt%.

[0060] Example 3

[0061] This embodiment provides a perovskite-molecular sieve composite material, including a molecular sieve and a perovskite material loaded in the molecular sieve, and the preparation method thereof is as follows:

[0062] 0.6 mol CsBr, 0.3 mol AgBr and 0.3 mol BiBr3 were dissolved in 12 mL organic solvent N,N-dimethylformamide (DMF), and 1.2 g ZSM-5 molecular sieve (purchased from Luoyang Jianlong Micro-Nano New Materials Co., Ltd.) was added. The mixture was heat treated at 80°C for 3 h under stirring. The solid product was separated by centrifugation, washed with water and ethanol for 5 times, and then heat treated at 260°C for 3 h to obtain a perovskite-molecular sieve composite material with a D50 particle size of 300 nm and a perovskite material (Cs2AgBiBr6) content of 1.3 wt%.

[0063] Example 4

[0064] This embodiment provides a perovskite-metal organic framework (MOFs) composite material, including a metal organic framework (MOFs) and a perovskite material loaded in the metal organic framework (MOFs), and the preparation method thereof is as follows:

[0065] 0.85 mol CsI and 0.6 mol CuI were dissolved in 5 mL organic solvent N,N-dimethylformamide (DMF), and then 4 mL methanol was added. Then 1.1 g ZIF-8 metal organic framework (MOFs) (purchased from Xianfeng Nano) was added, and the mixture was heat treated at 100 °C for 3 h under stirring conditions. The solid product was separated by centrifugation, and washed with water and ethanol for 5 times, and then heat treated at 300 °C for 3 h to obtain a perovskite-metal organic framework composite material. 50 The particle size is 300nm and the content of perovskite material (Cs3Cu2I5) is 0.5wt%.

[0066] Example 5

[0067] This embodiment provides a perovskite-metal organic framework composite material, including a metal organic framework (MOFs) and a perovskite material loaded in the metal organic framework (MOFs), and the preparation method thereof is as follows:

[0068] 0.85 mol CsI and 0.6 mol CuI were dissolved in 5 mL organic solvent N, N-dimethylformamide (DMF), and then 4 mL methanol was added. Then 1.1 g of materials of Institute Lavoisier (MILs) (purchased from Xianfeng Nano) was added, and the mixture was heat treated at 100 ° C for 3 h under stirring conditions, and the solid product was separated by centrifugation. The solid product was washed with water and ethanol for 5 times, and then heat treated at 300 ° C for 3 h to obtain a perovskite-metal organic framework composite material with a D50 particle size of 400 nm and a perovskite material (Cs3Cu2I5) content of 1.1 wt%.

[0069] Example 6

[0070] This embodiment provides a perovskite-metal organic framework composite material, including a metal organic framework (MOFs) and a perovskite material loaded in the metal organic framework (MOFs), and the preparation method thereof is as follows:

[0071] 0.85molCsI and 0.6molCuI were dissolved in 5mL organic solvent N,N-dimethylformamide (DMF), and then 4mL methanol was added. Then 1.1g of pocket-channel frameworks (PCNs) (purchased from Xianfeng Nano) was added, and the mixture was heat treated at 100℃ for 3h under stirring conditions. The solid product was separated by centrifugation, and washed with water and ethanol for 5 times, and then heat treated at 300℃ for 3h to obtain a perovskite-metal organic framework composite material with a D50 particle size of 450nm and a perovskite material (Cs3Cu2I5) content of 2wt%.

[0072] Performance Test:

[0073] 1. Performance test of perovskite-molecular sieve composite materials

[0074] 1.1. In vitro anti-monkeypox virus performance test

[0075] The perovskite-molecular sieve composite material provided in Example 1-3 was uniformly dispersed in PBS buffer to form a 5 mg / mL suspension in the experimental group. 3.6 mL of the suspension was taken, 400 μL of monkeypox virus (GenBank: PP778666.1) stock solution was added, and the material was shaken at 1500 rpm to fully contact the virus. At the same time, a white light flashlight (irradiation intensity of about 10 mw / cm 2 ) were irradiated, and samples were taken after irradiation for 10 min, 40 min, and 90 min, and 100 μL of each sample was taken and diluted 10 times to 10 with serum-free and dual antibody-free DMEM medium. -1 ~10 -5 , 0.1 mL / well was inoculated into a 96-well plate of VeroE6 cells that had grown into a monolayer, 8 wells were inoculated for each dilution, and cultured in a 37°C, 5% CO2 incubator. Cytopathic effects were observed every day, and 3 consecutive days were the observation endpoint. TCID was calculated according to the Reed-Muench method 50 Value (half tissue cell infection dose). The difference between the positive control group 1 (PC) and the experimental group is that PBS buffer without composite materials is used instead of the suspension containing composite materials, and natural light is used instead of white light flashlight for irradiation. Other operations are the same as the experimental group. The difference between the positive control group 2 (PC-L) and the experimental group is that PBS buffer without composite materials is used instead of the suspension containing composite materials, and other operations are the same as the experimental group. Referring to the antiviral activity evaluation method specified in the ISO 21702 standard, the virus titer (log 10 TCID 50The ISO 21702 standard measures the reduction in the amount of virus in the test sample relative to the control sample. This reduction is called the R value, which is the difference between the amount of virus recovered in the control sample and the test sample, and is expressed as a logarithmic value with a base of 10.

[0076] The R value is calculated as follows:

[0077] R=(U t -U0)-(A t -U0)=U t -A t

[0078] Where:

[0079] R: Difference in antiviral logarithmic values;

[0080] U0: average virus titer recovered from samples of the control group at time 0;

[0081] U t : The average virus titer recovered from samples in the control group at time t;

[0082] A t : The average virus titer recovered from the experimental group samples at time t.

[0083] If R≥1, the test sample is considered to have a certain antiviral activity; R=1 is equivalent to a 90% reduction in the infectious virus in the test sample relative to the control sample; R=2 is a 99% reduction; R=3 is a 99.9% reduction, and so on.

[0084] It should be noted that the R value is a relative measurement (relative to the control sample). Because over time, the virus will naturally decay on any surface, resulting in a decrease in activity. Therefore, the virus reduction in the sample obtained in this experiment includes the "extra" virus inactivation effect caused by natural decay. There are also some other reasons for the relative reduction in virus activity rather than the absolute reduction, such as: laboratory conditions may vary from day to day, and the viruses used may also vary from batch to batch.

[0085] The experimental results are as follows Figure 1 As shown. Figure 1It can be seen that the composite materials with a mass percentage of 1.7% and 0.7% perovskite provided in Examples 1 and 2 can achieve a 99.99% inactivation rate against monkeypox virus within 10 minutes of illumination, but in comparison, the corresponding composite material of Example 1 has a higher disinfecting activity. When the perovskite composition is exactly the same (Cs3Cu2I5), the disinfecting activity is proportional to its mass percentage. The composite material with a mass percentage of 1.3% perovskite (Cs2AgBiBr6) provided in Example 3 can achieve a 99.9% inactivation rate against monkeypox virus within 30 minutes of illumination.

[0086] 1.2 Effect of perovskite-molecular sieve composites on the structure of monkeypox virus

[0087] The perovskite-molecular sieve composite material provided in Example 1 was uniformly dispersed in PBS buffer to form a 5 mg / mL suspension, and then a stock solution of monkeypox virus (GenBank: PP778666.1) (containing two morphologies, oval and elliptical) was added, and the material and the virus were fully contacted at 1500 rpm. While shaking, a white light flashlight (irradiation intensity of about 10 mw / cm 2 ) were irradiated, and samples were taken at 5 minutes, 10 minutes, 30 minutes, and 1 hour after the start of shaking. The morphology of monkeypox virus particles before and after treatment was observed by negative staining using a transmission electron microscope (TEM). The results are shown in Figure 2 As shown. Among them, Figures a and f are normal monkeypox virus particles, which are divided into two common morphologies: oval (Figure a) and elliptical (Figure b), Figures b, c, d, and e are oval monkeypox virus particles after being treated with perovskite-molecular sieve composite materials for 5 minutes, 10 minutes, 30 minutes, and 1 hour, respectively, and Figures g, h, i, and j are elliptical monkeypox virus particles after being treated with perovskite-molecular sieve composite materials for 5 minutes, 10 minutes, 30 minutes, and 1 hour, respectively.

[0088] from Figure 2 It can be seen that normal monkeypox virus generally presents an oval or ellipsoid shape and has a complete capsule structure. The degree of damage to the capsule of the monkeypox virus after being treated with the perovskite-molecular sieve composite material provided in Example 1 for 5 minutes, 10 minutes, 30 minutes, and 1 hour gradually increases, which shows that the material can achieve the effect of inactivating the virus by continuously destroying the shell structure of the monkeypox virus.

[0089] 1.3 Biosafety Testing

[0090] In order to ensure that the perovskite-molecular sieve composite material will not be toxic to organisms, an in vivo biosafety test was conducted. In this part of the experiment, balb / c mice were selected as experimental subjects. The experimental group of mice were injected with a solution of the perovskite-molecular sieve composite material provided in Example 1 (the solvent was 1M, pH = 7.4 PBS buffer) at a concentration of 5 mg / mL through the tail vein, and the control group was injected with 1M, pH = 7.4 PBS buffer. The weight changes of the mice were observed for 12 consecutive days after the injection. The results are as follows: Figure 3 As shown. After the experiment, the mice were killed, and the heart, liver, spleen, lung, and kidney were taken and stored in 4% paraformaldehyde solution for more than 24 hours. The tissue samples were taken out of the fixative, and the target tissue was trimmed with a scalpel in the fume hood. The trimmed tissue and the corresponding label were placed in the dehydration box. The dehydration box was placed in the hanging basket in the dehydrator, and the gradient dehydration treatment was carried out in the order of 75% alcohol for 4 hours, 85% alcohol for 2 hours, 90% alcohol for 2 hours, 95% alcohol for 1 hour, anhydrous ethanol I for 30 minutes, anhydrous ethanol II for 30 minutes, alcohol benzene for 10 minutes, xylene I for 10 minutes, xylene II for 10 minutes, wax I for 1 hour, wax II for 1 hour, and wax III for 1 hour. The trimmed wax block was placed on a paraffin slicer and sliced ​​with a thickness of 4 μm. The slices were floated on the 40°C warm water of the spreader to flatten the tissue, and the tissue was picked up with a slide and placed in a 60°C oven for baking. After the water-dried wax is baked and melted, take it out and store it at room temperature for later use. Then the paraffin sections are dewaxed and hydrated, and the nuclei are stained with hematoxylin and the cytoplasm is stained with eosin. After dehydration and sealing, the images are collected under a microscope. Figure 4 As shown, Figure A is the control group and Figure B is the experimental group.

[0091] from Figure 3 It can be seen that the weight of mice in both the control group and the experimental group increased steadily, with almost no difference. Figure 4 It can be seen that no obvious pathological changes were found in the heart, liver, spleen, lung and kidney of mice in the control group and the experimental group, which confirmed that the perovskite-molecular sieve composite material had no effect on the organ tissues of mice. The above experimental results show that the perovskite-molecular sieve composite material has good biosafety.

[0092] 1.4. Therapeutic effects of monkeypox virus infection in mice

[0093] Five-week-old C57 male mice were selected, and the stock solution of monkeypox virus (GenBank: PP778666.1) was diluted 10 times. After the mice were anesthetized, 10 μL of virus droplets were taken on the dorsal side of the mouse tail (1 cm away from the base of the tail), and a 1 mL syringe needle was used to pass through the virus liquid and repeatedly scratched 20-30 times to form a tail scratch of about 1 cm in length, thereby constructing a monkeypox virus-infected mouse tail scratch model. The perovskite-molecular sieve composite material provided in Example 1 was mixed with methacrylated gelatin hydrogel to prepare a composite material @ hydrogel dressing, and the dressing was placed in a 37°C water bath for 1 min to melt into a liquid state before use. An appropriate amount of liquid dressing was applied around the pockmarks on the tail of the mice in the experimental group, and an ultraviolet lamp was used to irradiate for 1 min to cross-link the liquid dressing, and then a visible light flashlight (irradiation intensity was about 10 mw / cm 2 ) irradiate the dressing for 10 minutes. Repeat the above experimental operation for three consecutive days to observe the healing of the affected area of ​​the mouse tail. The mice in the positive control group were only exposed to light under the same conditions as the experimental group after infection. After the experiment, the mice were killed, and the lesion area of ​​the mouse tail was cut for pathological section analysis. Hematoxylin was used to stain the nucleus and eosin was used to stain the cytoplasm. After dehydration and sealing, images were collected under a microscope. The results are shown in the figure. Figure 5 shown.

[0094] Figure 5 Figure 2 is a staining image of the pathological sections of the tail lesion area of ​​mice in the positive control group and the experimental group, where Figure a is the positive control group and Figure b is the experimental group. Figure 5 It can be seen that the tail tissue structure of the mice in the positive control group is severely abnormal, with epithelial erosion and ulceration in some areas, and a large number of necrotic neutrophils and protein mucus can be seen, as shown by the red arrow; the spinous layer is thickened and the cells are arranged in disorder, as shown by the black arrow; the number of collagen fibers in the dermis is reduced and arranged loosely, and a large number of inflammatory cells can be seen infiltrating, as shown by the green arrow. The tail tissue structure of the mice in the experimental group is slightly abnormal, the epidermal structure is relatively complete, and the spinous layer is thin, as shown by the red arrow; the collagen fibers in the dermis are reduced, and a large number of inflammatory cells can be seen infiltrating, as shown by the green arrow; the yellow arrow indicates the hair follicle, the blue arrow indicates the muscle fiber, and the black arrow indicates the bone formation. It shows that the perovskite-molecular sieve composite material has a good therapeutic effect on mice infected with monkeypox virus.

[0095] 1.5. Therapeutic effect of monkeypox virus infection in rabbits

[0096] New Zealand male rabbits weighing about 2.5 kg were selected as the subjects of monkeypox virus infection to further simulate the treatment process after monkeypox skin wounds. After the experimental rabbits were anesthetized, the hair on their backs was removed and 10 inoculation areas were evenly divided. After disinfection, 50 μL of monkeypox virus (GenBank: PP778666.1) stock solution was subcutaneously inoculated in each area, and the lesions in the inoculated areas were observed. In the experiment, the 5 inoculation areas on the left side of the experimental rabbit's back were used as the positive control group, and the 5 areas on the right side were used as the experimental group. After the acne spots appeared, the experimental group was treated with composite material @ hydrogel dressing (the same as the dressing in the experiment of "1.4, Therapeutic effect of monkeypox virus infection on mice"), and the dressing was placed in a 37°C water bath for 1 minute to melt into a liquid state, and an appropriate amount of liquid dressing was evenly applied around the acne spots in the experimental group. The liquid dressing was cross-linked by ultraviolet light for 1 minute, and then a visible light flashlight (irradiation intensity was about 10mw / cm 2 ) irradiate the dressing for 10 minutes. Repeat the above experimental operation for three consecutive days to observe the healing of the affected area on the back of the experimental rabbit. The positive control group was inoculated with monkeypox virus and then irradiated with light under the same conditions as the experimental group. The results are as follows Figure 6 As shown, Figure a shows the lesions on the back of the experimental rabbit on the 0th day before treatment with the composite material@hydrogel dressing, Figure b shows the lesions on the back of the experimental rabbit on the 3rd day after treatment with the composite material@hydrogel dressing, and Figure c is a local picture of the lesion area on the back of the experimental rabbit on the 3rd day after treatment with the composite material@hydrogel dressing.

[0097] from Figure 6 (a) shows that the acne spots in the left area scab over to form a localized mass; while (b, c) show that the acne spots in the right area disappear after the perovskite-molecular sieve composite material is applied and illuminated, and almost no scars are left. This shows that the perovskite-molecular sieve composite material has a good therapeutic effect on rabbits infected with monkeypox virus.

[0098] Traditional clinical treatments for monkeypox mainly use the method of "painkillers + surgical debridement" to remove the infected parts of monkeypox, which undoubtedly brings great pain to patients, increases the risk of infection and prolongs the time of wound healing. Based on the above experimental results, the perovskite-molecular sieve composite material provided by the present invention is expected to achieve the treatment of monkeypox virus infection through mild treatment methods (external application + short-term light exposure), without causing secondary harm to patients, and reducing the pain of patients as much as possible. It blocks the spread of the virus while debridement and minimizes the risk of infection.

[0099] 2. Performance test of perovskite-MOFs composite materials

[0100] 2.1. Viruses used in the experiment

[0101] SARS-CoV-2 novel coronavirus wild-type isolate (BetaCoV / Beijing / IME-BJ01 / 2020) and its Beta variant (CSTR:16698.06.NPRC2.062100001), Delta variant (CSTR:16698.06.NPRC6.CCPM-8-V-049-2105-6), Omicron BA.1 (SARS-CoV-2 strain OmicronCoV / human / CHN_CVRI-01 / 2022), Omicron BA.2 (SARS-CoV-2 strain OmicronCoV / human / CHN_CVRI-04 / 2022). All the above strains were isolated, passaged and virus titer was determined using Vero E6 cells. Influenza virus (H1N1, H3N2) isolates, Japanese encephalitis virus (JEV) isolates, vesicular stomatitis virus with green fluorescent protein inserted (VSV-GFP) isolates, adenovirus (ADV) isolates, Seneca virus (SVA) isolates, human coronavirus (HCoV-OC43) isolates, transmissible gastroenteritis virus (TGEV) strains, porcine epidemic diarrhea virus (PEDV) strains, and vaccinia virus (VTT) strains.

[0102] 2.2. Broad-spectrum antiviral experiment

[0103] In order to verify the broad-spectrum antiviral performance of perovskite-MOFs composite materials, representative viruses were selected for experiments, such as SARS-CoV-2 wild strains and their variants, HCoV-OC43, TGEV, PEDV, H1N1, H3N2 and other types of coronaviruses, which are enveloped RNA viruses; JEV, VSV and VTT (poxviruses of the same family and genus as monkeypox virus), which are enveloped DNA viruses; ADV, which is a non-enveloped DNA virus; SVA, which is a non-enveloped RNA virus. These viruses can be divided into enveloped / non-enveloped, DNA / RNA, airborne / waterborne / fecal-oral transmission according to their structure, genetic material and transmission mode, which meets the needs of broad-spectrum detection in the selection of virus types.

[0104] The perovskite-MOFs composite materials provided in Examples 4-6 (referred to as MOF-1, MOF-2, and MOF-3, respectively) were dispersed in PBS buffer at a concentration of 5 mg / mL, and rapidly oscillated at 1500-8500 rpm for 5-30 min to form a suspension. Add 3.6 mL of suspension and 400 μL of virus stock solution to each tube, and oscillate the mixed solution on a rapid oscillator under natural light conditions to allow the composite material to fully contact the virus particles. Then, 100 μL of supernatant was taken at different time points (5 min, 30 min, 1 h, 4 h) and diluted in a 10-fold gradient. The sample was then added to a 96-well culture plate covered with a monolayer of confluent cells at 0.1 mL / well and incubated in a 37°C, 5% CO2 incubator for 48-72 h (depending on the cell growth rate). The degree of cytopathic effect (CPE) was observed under a light microscope. TCID was calculated using the Reed-Muench method. 50 This section selects ISO 21702 and WS / T 775-2021 standards as test methods for evaluating the antiviral properties of perovskite-MOFs composite materials. The antiviral effects of perovskite-MOFs composite materials when in contact with viruses for 5 minutes are shown in Table 1.

[0105] Table 1

[0106]

[0107]

[0108]

[0109] In Table 1, a: Test method for antiviral activity of materials (ISO 21702); b: Virus titer in log 10 TCID 50 / mL, detection limit is 2log 10 TCID 50 / mL; c: antiviral activity value (Mv); d: antiviral efficiency is determined by Mv (Mv = 2.0: 99%; Mv = 3.0: 99.9%; Mv>3.0: 99.99%); in the antiviral activity test, the antiviral effect of 3.0>Mv≥2.0 is defined as good, and the antiviral effect of Mv>3.0 is defined as excellent. It should be noted that the virus titer detection limit of this experiment is 2log 10 TCID 50 / mL, since the virus liquid has been diluted 10 times for the first time when it comes into contact with the composite material, and it has been diluted 10 times for the second time when it is inoculated in the 96-well plate, if you want to achieve an antiviral efficiency of 99.99%, according to the ISO standard, the toxicity of the original virus must be greater than or equal to 5, only in this way can their difference be greater than 3. Taking the Omicron strain of the new coronavirus as an example, it is highly contagious but weakly pathogenic, so its toxicity is very low and cannot reach 5, and it cannot be achieved after ultracentrifugation concentration, so these viruses cannot be judged according to the ISO standard whether they have achieved an antiviral efficiency of 99.99%, but according to the inactivation of the composite material on the strongest wild strain in the new coronavirus family, theoretically, it will have exactly the same effect on the Omicron strain, so there is a situation in Table 1 where the Mv value is less than 3 and the antiviral efficiency is greater than 99.99%.

[0110] Since enveloped viruses are very sensitive to changes in environmental physical and chemical factors (temperature, pH, presence or absence of ultraviolet rays, etc.), it is much more difficult to disinfect enveloped viruses than non-enveloped viruses. As can be seen from Table 1, the perovskite-MOFs composite material (MOF-3) provided in Example 6 has the best virus inactivation effect under natural light conditions, and the inactivation rate can reach more than 99.9% after contacting with SARS-CoV-2 and other viruses for 5 minutes.

[0111] 2.3 Flow cytometry

[0112] This section uses VSV-GFP as a model virus. The virus has the characteristics of high viral titer, broad infection spectrum, and different reproduction rates in different cells. Appropriate susceptible cells can be selected according to different experimental conditions.

[0113] The perovskite-MOFs composite materials provided in Examples 4-6 (recorded as MOF-1, MOF-2, and MOF-3, respectively) were dispersed in PBS buffer at a concentration of 5 mg / mL, and rapidly oscillated at 1500-8500 rpm for 5-30 min to form a suspension. 3.6 mL of suspension and 400 μL of VSV-GFP virus stock solution were added to each tube, and the mixed solution was oscillated on a rapid oscillator under natural light conditions to allow the composite material to fully contact the virus particles. Then, 100 μL of supernatant was taken at different time points (5 min, 30 min, 1 h, 4 h, 24 h) and diluted in a 10-fold gradient. Then, the sample was added to a 96-well culture plate filled with A549 cells at 0.1 mL / well, and the sample was taken after incubation in a 37°C, 5% CO2 incubator for 12-16 hours (experimental experience shows that VSV-GFP virus begins to infect A549 cells after 1 hour of incubation, and the expression rate of green fluorescent protein (GFP) reaches more than 70% after 12 hours of incubation. Therefore, it is necessary to pay attention to the cell state after 12 hours of incubation to determine the best sampling time point.). The difference between the positive control group and the experimental group is that PBS buffer without composite materials is used instead of the suspension containing composite materials, and other operations are the same as the experimental group. The difference between the negative control group and the experimental group is that 4 mL of suspension is added to each tube, and no VSV-GFP virus stock solution is added, and other operations are the same as the experimental group. The expression level of GFP protein in cells was observed using the EVSO M5000 single-cell microscopic mobile platform, and the fluorescence rate of samples at different time periods was detected by flow cytometry.

[0114] After VSV-GFP infects A549 cells for 12–16 hours, use a single-cell microscopic mobile platform to observe the proportion of green fluorescence in the positive control (PC) group occupying the entire well. When the green fluorescence of the positive control group fills the field of view, you can start preparing a single-cell suspension. Add trypsin / EDTA digestion solution (150 μL) (0.25%) to the 6-well plate, digest at room temperature for 1 minute, add RPMI 1640 medium (1 mL) to terminate the digestion, and centrifuge and discard the supernatant. Add PBS (1 mL) to the 2 mL centrifuge tube containing the cell mass at the bottom and wash repeatedly 3 times. Finally, use 500 μL PBS to prepare a single-cell suspension and store it in a refrigerator at 4°C for detection.

[0115] The results of green fluorescence quantification by flow cytometry are shown in Figure 7 As shown, ***p<0.001, **p<0.01, *p<0.05.

[0116] from Figure 7It can be seen that the changing trend of the fluorescence rate is exactly the same as that observed by the naked eye. The negative control group (Mock) did not produce green fluorescence when not in contact with the VSV-GFP virus, indicating that the cell line was not contaminated. From 5 minutes of contact, the VSV-GFP virus treated with MOF-2 (Example 5) and MOF-3 (Example 6) showed almost no expression of green fluorescent protein compared with the positive control group (PBS), while the VSV-GFP virus only significantly lost the ability to express green fluorescent protein after contacting with MOF-1 (Example 4) for 4 hours. Considering the effect of the structural stability of the material on the long-term antiviral performance, it is obvious that the perovskite-MOFs composite material (MOF-3) provided in Example 6 has better application potential.

[0117] 2.4. Golden hamster nose drop test

[0118] Because the spike protein structure of SARS-CoV-2 is unstable and prone to mutation, it can not only be transmitted through air, water, etc., but also survive for a long time on the surface of various solid materials, making it highly contagious. In order to further prove that the virus treated with the perovskite-MOFs composite material provided in Examples 4-6 is no longer pathogenic in the biological tissue environment, and to further verify that it has good biocompatibility, a golden hamster nasal drop experiment was conducted.

[0119] 4-6 week old male golden hamsters were selected as animal models for SARS-CoV-2 infection. The perovskite-MOFs composite materials provided in Examples 4-6 (referred to as MOF-1, MOF-2, and MOF-3 in sequence) were uniformly dispersed in PBS buffer to form a 5 mg / mL suspension. 3.6 mL of the suspension was mixed with 400 μL of SARS-CoV-2 virus stock solution. Under natural light conditions, the mixed solution was oscillated on a fast oscillator to allow the composite material to fully contact the virus particles. After 10 minutes, the supernatant was centrifuged at 5000-8000 rpm. After anesthetizing the golden hamsters with isoflurane, 50 μL of sample (3.5×10 4 The difference between the control group and the experimental group was that PBS buffer without composite materials was used instead of the suspension containing composite materials, and other operations were the same as the experimental group. The mice were killed 3 days after infection (3DPI), and the nasal turbinates, trachea and lung tissues of the mice were separated, and tissue homogenates were prepared for virus titration to observe the degree of lung tissue lesions induced by SARS-CoV-2. The results are shown in Figure 8 shown.

[0120] from Figure 8The results of virus titration in tissue homogenates show that SARS-CoV-2 mainly reproduces in the lung tissue after infecting the golden hamster, and the viral load in the lung tissue is much higher than that in the nasal concha and trachea. The reproduction capacity of SARS-CoV-2 in the nasal concha, trachea and lung tissue of the golden hamster treated with MOF-3 (Example 6) for 5 minutes is significantly reduced, and the tissue homogenate contains almost no pathogenic SARS-CoV-2 virus.

[0121] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A perovskite-porous carrier composite material, characterized in that: The composite material comprises: a porous support, and a perovskite material loaded in the porous support.

2. The composite material according to claim 1, characterized in that In the composite material, the mass content of the perovskite material is 0.1-2%; Preferably, the particle size of the composite material is 100-500 nm.

3. The composite material according to claim 1 or 2, characterized in that: The perovskite material includes one or more of an oxide perovskite material, a halide perovskite material, a double perovskite material and an antiperovskite material; Preferably, the perovskite material is selected from one or more of ABX3, A2BX6, A3B2X5 and A2BX4, wherein A is selected from one or more of La, Ce, Cs, FA and MA, B is selected from one or more of Fe, Mn, Bi, Ag, In and Ti, and X is selected from one or more of O, Br, Cl and I; Preferably, the perovskite material is selected from one or more of LaFeO3, Cs2AgInCl6, Cs2AgBiBr6, MA2AgSbI6, Cs3Cu2I5 and CeMnO3.

4. The composite material according to any one of claims 1 to 3, characterized in that: The porous carrier includes one or more of a molecular sieve, an inorganic mesoporous material and an inorganic macroporous material; Preferably, the porous carrier is selected from one or more of molecular sieves and metal organic frameworks.

5. The composite material according to claim 4, characterized in that The pore size of the molecular sieve is less than 2 nm, and the molecular sieve includes one or more of X, Y type molecular sieve, A type molecular sieve, silicate-1 molecular sieve, ZSM-5 molecular sieve and beta molecular sieve; Preferably, the pore size of the inorganic mesoporous material is 2-50 nm, and the inorganic mesoporous material includes one or more of mesoporous silicon, mesoporous metal organic framework, mesoporous covalent organic framework and mesoporous metal oxide; Preferably, the pore size of the inorganic macroporous material is greater than 50 nm, and the inorganic macroporous material comprises one or more of a macroporous metal organic framework, a macroporous ceramic and a macroporous oxide; Preferably, the metal organic framework comprises one or more of a repeating network metal organic framework, a zeolite imidazolate framework, a Lavoisier Materials Institute framework and a pore-through framework material.

6. A method for preparing the perovskite-porous carrier composite material according to any one of claims 1 to 5, characterized in that: The preparation method is a solution method or a solid phase calcination method; The solution method comprises: dissolving a precursor of a perovskite material in an organic solvent, mixing the mixture with a porous carrier, performing a first heat treatment to allow the precursor to enter the pores of the porous carrier, separating a solid product, and performing a second heat treatment to convert the precursor into a perovskite material to obtain the perovskite-molecular sieve composite material; The solid phase calcination method comprises: mixing a precursor of a perovskite material with a porous carrier, and calcining the mixture to obtain the perovskite-porous carrier composite material.

7. The preparation method according to claim 6, characterized in that: The organic solvent includes N,N-dimethylformamide and / or dimethyl sulfoxide; Preferably, the temperature of the first heat treatment is 30-200°C and the time is 2-4h; Preferably, the temperature of the second heat treatment is 200-500°C and the time is 1-4h; Preferably, the solution method further comprises: washing the solid product before performing the second heat treatment; Preferably, the solvent used for the washing comprises water and / or ethanol.

8. The preparation method according to claim 6, characterized in that: The calcination temperature is 500-800°C and the calcination time is 4-8h.

9. Use of the perovskite-porous carrier composite material as described in any one of claims 1 to 5, or the perovskite-porous carrier composite material prepared by the preparation method as described in any one of claims 6 to 8, in the preparation of antibacterial and antiviral products, anti-tumor drugs, bioimaging agents or thermal diagnosis and treatment photothermal agents.

10. The use according to claim 9, characterized in that: The antibacterial and antiviral products include disinfectants and wound dressings; Preferably, the types of bacteria and viruses targeted by the antibacterial and antiviral products include: Staphylococcus aureus, Helicobacter pylori, Escherichia coli, Bacillus anthracis, Brucella, Clostridium tetani, Treponema pallidum, herpes virus, hepatitis B virus, HIV, hemorrhagic fever virus, influenza virus, new coronavirus, and monkeypox virus.

Citation Information

Cited By

  • Application of InNNi3 in preparation of antibacterial product

    CN120837640A

  • Antibacterial material with calcium ion mediation and photo-thermal effects as well as preparation method and application of antibacterial material

    CN121975144A